Galois field operational unit for Elliptic Curve Cryptography Digital Signature - Rahma, Mohammed Kadhim (Lviv Polytechnic Publishing House, 2015)
Cryptography is the most standard and efficient way to protect the security of data transactions. An efficient cryptosystem must be one that is strong enough to ensure a high level of security for reliable transmission of information. Elliptic curve cryptography is one such type of public key and private key cryptosystem based on small key size with high efficient speed up of cryptography process. Elliptic curve cryptography is an alternative to traditional techniques for public key cryptography. It can be called the future generation of public key systems since it involves less number of bits suitable for resource constrained and wireless applications without compromising on the security level. The proposed architecture for elliptic curve scalar is based on Point multiplication algorithm. It was also generated (Extension Field) assimilation by EF(387) where GF(2173)& EF(387) fields have approximately the same number of elements, and results were compared and implemented.
Keywords: Galois field GF(2n); Extension Field EF(pm); Elliptic Curve Cryptography; Digital Signature; Operational unit for scalar multiplication